Zn / Fe co-doped SnO2 ultrathin hollow edge nanocage superstructure composite material as well as preparation method and application thereof
Through Zn/Fe co-doped SnO2 ultra-thin hollow edge nanocage superstructure composite material, the problem of insufficient sensitivity and response speed of traditional gas sensors is solved, and high sensitivity detection and rapid response to H2S gas is achieved.
Patent Information
- Application Number
- CN202411892735.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
When existing gas sensors detect toxic and harmful gases, their sensitivity and response speed are insufficient, and traditional biboshell/multi-shell nanomaterials with insufficient utilization of active sites in chemical reactions.
The Zn/Fe co-doped SnO2 ultra-thin hollow edge nanocage superstructure composite material was used, and the zinc-iron Prussian blue nanocage was used as a hard template and combined with annealing process to prepare a material with a unique hollow edge and open cage-like cavity structure.
High sensitivity detection of H2S gas is achieved, with fast response/recovery time, good reversibility and long-term stability, and the selectivity of H2S is significantly better than other reducing gases.
Smart Images

Figure CN119750637A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material and a preparation method and application thereof. Background Art
[0002] Air quality issues remain a major concern in many countries. A clean air supply is essential for our health and environment. The human nose is a highly advanced perception system that can distinguish hundreds of odors, but it fails if absolute gas concentrations or odorless gases need to be detected. Therefore, the demand for the detection of toxic and hazardous gases urgently needs to support or replace the human nose. Although a large number of gas detection systems have been used in process control and laboratory analysis, in order to improve the level of gas detection, high-performance gas sensors with high sensitivity, high selectivity and fast response speed are also needed.
[0003] Metal oxide gas sensors have been widely used in portable gas detection systems due to their low cost, ease of fabrication, small size, and simple measuring electronics. However, the performance of such sensors is significantly affected by the morphology and structure of the sensing material, resulting in great obstacles in achieving high sensitivity performance for gas sensors based on bulk materials or dense films. Nanomaterial gas sensors are an important development direction for improving gas sensitivity, selectivity, and response speed.
[0004] Metal oxide semiconductors have been widely studied for H2S sensors due to their compatibility with microelectronic devices, simple manufacturing, economy, low operating cost, high response, and short response / recovery time. The sensitive materials for H2S detection reported in the literature include ZnO, SnO2, WO3, TiO2, CuO, Fe2O3, In2O3, and NiO. Among these materials, H2S sensors based on SnO2 nanostructures have shown excellent performance so far. As a broad-spectrum semiconductor, SnO2 has the advantages of simple preparation, short response and recovery time, and high sensitivity compared to other semiconductor gas-sensitive materials.
[0005] Up to now, people have prepared many SnO2 materials with different structures for the detection of toxic and harmful gases. Among various gas sensors, metal oxide semiconductor gas sensors are particularly concerned. Metal oxide semiconductor gas sensors detect gas by using the change in resistance when the gas contacts the surface of the sensing material. Compared with other gas sensors, it has the advantages of low cost, long life, high stability, and wide measurement range. SnO2 is an n-type wide bandgap semiconductor (Eg = 3.6eV at 300K) with the advantages of high gas sensitivity, high chemical stability, and low cost. It is well known that the gas-sensing performance of SnO2 depends on its morphology. In addition, the loading of metals or metal oxides (Ag, Pt, Pd, CuO, NiO, etc.) can improve gas sensitivity. Hollow porous SnO2 with unique structural characteristics has received considerable attention in many applications such as gas sensors. Porous structures can effectively increase the specific surface area and porosity of materials; large specific surface area can provide sufficient active sites to improve the gas adsorption capacity of the material surface, and large porosity can help accelerate the diffusion of target gas molecules in the material, which is beneficial to the improvement of the gas sensing performance of the material. In addition, increasing the complexity of nanomaterials in structure and composition is also an effective way to improve the chemical properties of gas-sensitive materials.
[0006] With the development of materials science and nanotechnology, more and more complex superstructure nanomaterials have been prepared and achieved ideal chemical properties. For example, Fu et al. combined the Marangoni effect to convert ZIF-67 nanocubes into ZIF-L open nanocages, providing a new perspective for the preparation of complex nanostructures; Lou's team used tannic acid etching and cation exchange processes to prepare Cu-substituted Mn-PBAs double-shell nanoboxes and applied them to zinc-ion batteries. The unique hollow nanostructure can not only provide abundant active sites and large specific surface area, but also adapt to large structural changes during ion insertion / deinsertion, thereby improving battery capacity and cycle stability; Zheng et al. used a multi-step deposition strategy to controllably prepare SnO2 three-shell hollow boxes with a clear cubic shape. Compared with the reference single-shell and double-shell SnO2 nanoboxes, the gas-sensitive response performance of the SnO2 three-shell hollow box was significantly improved, and the response / recovery time was shortened.
[0007] Even though the above work has greatly expanded the complexity of nanomaterials, traditional double-shell / multi-shell structures are mostly closed structures, which are not conducive to the diffusion and transmission of target reactants. During chemical reactions (especially surface reactions), the probability of the inner shell contacting the target reactants is limited, which is not conducive to the full utilization of active sites. Due to the difficulties in design and preparation, relevant reports on hollow edge nanocage superstructures with more complex open structures have not yet been found. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material and its preparation method and application. The material has a unique hollow rib and a completely open cage-like cavity structure. The gas-sensitive test results show that the sensor based on the SnO2 hollow rib nanocage has a relatively low operating temperature, a fast response / recovery time, good reversibility and long-term stability, and the selectivity for H2S is significantly better than other reducing gases.
[0009] The technical solution adopted by the present invention is as follows:
[0010] A method for preparing a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material, characterized in that the preparation method comprises the following steps:
[0011] (1) preparing a zinc iron Prussian blue nanocube precursor and dispersing it in deionized water for aging to obtain a zinc iron Prussian blue nanocage;
[0012] (2) dispersing zinc iron Prussian blue nanocages in deionized water to form a suspension A, dissolving stannous salt in concentrated hydrochloric acid to form a solution B, pouring the solution B into A under stirring, stirring evenly, and standing at 30-180° C. for 3-24 hours to obtain a tin-coated zinc iron Prussian blue nanocage ultra-thin hollow edge nanocage material;
[0013] (3) The tin-coated zinc-iron Prussian blue nanocage ultrathin hollow rim nanocage material is annealed at 280-550°C for 1-5h to obtain a Zn / Fe co-doped SnO2 ultrathin hollow rim nanocage superstructure composite material.
[0014] In step (1), the preparation method of the zinc-iron Prussian blue nanocube precursor is: dissolving zinc salt in dilute hydrochloric acid, adding potassium ferrocyanide aqueous solution thereto, stirring until the solution becomes a yellow suspension, standing and aging at 10-95° C. for 2-36 hours, filtering, washing and drying.
[0015] Furthermore, the zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate and zinc nitrate; and the molar ratio of potassium ferrocyanide to zinc salt is 1:1.
[0016] The concentration of the potassium ferrocyanide aqueous solution is 0.1-2.0 mol / L; the concentration of the zinc salt in the dilute hydrochloric acid is 0.1-2.0 mol / L; and the concentration of the dilute hydrochloric acid is 0.1-1.2 mol / L.
[0017] The static aging condition is preferably 60-80° C. for 12-24 hours.
[0018] In step (1), the standing and aging time is 1 to 5 days.
[0019] In step (2), the stannous salt is one or both of stannous chloride and stannous sulfate.
[0020] In step (2), the mass ratio of zinc iron Prussian blue nanocage to stannous salt is 1:0.3-1.5.
[0021] In step (2), the concentration of zinc iron Prussian blue nanocages in deionized water is 0.4-20 mg / mL.
[0022] In step (2), the concentration of stannous salt in concentrated hydrochloric acid is 3.0-15.0 mg / mL; the concentration of concentrated hydrochloric acid is 10-12 mol / L.
[0023] In step (3), the annealing condition is preferably 320-400° C. for 2-3 hours.
[0024] In step (3), the heating rate to the specified annealing temperature is 1 to 6°C / min, preferably 1 to 2°C / min.
[0025] The invention also provides a Zn / Fe co-doped SnO2 ultra-thin hollow rib nano cage superstructure composite material prepared by the preparation method.
[0026] The present invention also provides the application of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nano cage superstructure composite material in a gas sensor. When used as a gas-sensitive material of a gas sensor, the composite material has a high sensitivity to hydrogen sulfide gas and good stability.
[0027] In the preparation method disclosed by the present invention, zinc iron Prussian blue nanocubes that are easy to prepare are used as precursors, and zinc iron Prussian blue nanocages are obtained through aging. After coating, tin-coated zinc iron Prussian blue nanocage ultra-thin hollow ridge nanocage materials are obtained. After high-temperature calcination, Zn / Fe co-doped SnO2 ultra-thin hollow ridge nanocage superstructure composite materials are obtained.
[0028] Some of the chemical reaction formulas involved in the reaction process are shown below:
[0029] 3Zn 2+ + 3[Fe(CN)6] 3- → Zn3[Fe(CN)6]2 (1)
[0030] 21Sn 2+ + 20H2O +16Cl - → Sn 21 Cl 16 (OH) 14 O6 + 26H + (2)
[0031] Sn 21 Cl 16 (OH) 14 O6 + 11O2 → 21SnO2+ 14HCl+ Cl2 (3)
[0032] The preparation method of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material provided by the present invention is simple. With Zn-Fe Prussian blue open nanocage as a hard template, in the absence of additional surfactants or protective agents, combined with an annealing process, the controllable preparation of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material is realized for the first time. The combination of the nanoscale cavity and the chemical function of the porous ultra-thin shell layer makes the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material have the characteristics of uniform pore size, large specific surface area, sufficient active sites, small crystal size, etc.
[0033] The sensor devices prepared based on this material have high sensitivity and good anti-interference performance. The study of gas sensing mechanism shows that during the H2S gas sensing response process of Zn / Fe co-doped SnO2 hollow prism nanocages, the chemically adsorbed oxygen on the surface of the material and the material itself react with H2S. The synergistic effect of the surface adsorbed oxygen and the formation of metastable sulfides at the particle interface makes the material exhibit excellent gas sensing performance to H2S. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM image of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material prepared in Example 1;
[0035] Figure 2 This is a SEM image of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material prepared in Example 2;
[0036] Figure 3 This is a SEM image of the zinc iron Prussian blue nanocube precursor prepared in Example 3;
[0037] Figure 4 This is the XRD pattern of the zinc iron Prussian blue nanocube precursor prepared in Example 3;
[0038] Figure 5 This is a SEM image of the zinc-iron Prussian blue nanocage prepared in Example 3;
[0039] Figure 6 This is the XRD pattern of the zinc-iron Prussian blue nanocage prepared in Example 3;
[0040] Figure 7 This is a SEM image of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material prepared in Example 3;
[0041] Figure 8 The XRD pattern of the Zn / Fe co-doped SnO2 ultra-thin hollow prism nanocage superstructure composite material prepared in Example 3;
[0042] Fig. 9 This is an EDS image of the Zn / Fe co-doped SnO2 ultra-thin hollow edge nanocage superstructure composite material prepared in Example 3;
[0043] Fig.10 The BET diagram of the Zn / Fe co-doped SnO2 ultra-thin hollow prism nanocage superstructure composite material prepared in Example 3;
[0044] Fig.11 This is a SEM image of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material prepared in Example 4;
[0045] Fig.12 This is a SEM image of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material prepared in Example 5;
[0046] Fig.13 The response sensitivity of the Zn / Fe co-doped SnO2 ultra-thin hollow edge nanocage superstructure composite material prepared in Example 3 to 10 ppm H2S and 100 ppm of different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.) at an operating temperature of 130°C. DETAILED DESCRIPTION
[0047] The present invention is described in detail below with reference to the embodiments.
[0048] The reaction container used in step (2) in each embodiment is a beaker, and the mouth of the beaker is covered with plastic wrap during heating.
[0049] Example 1
[0050] A method for preparing a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material comprises the following steps:
[0051] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of 2M potassium ferrocyanide solution; zinc chloride is dissolved in 0.1M dilute hydrochloric acid to prepare 1000 mL of 2M zinc chloride solution; the potassium ferrocyanide solution is added to the zinc chloride solution under magnetic stirring at a speed of 150 rpm, and then stirring is continued at room temperature for 50 min to obtain a mixed suspension, which is allowed to stand for 2 h at 99° C. to obtain a yellow precipitate, which is filtered, washed, and dried at 100° C. for 6 h to obtain a zinc iron Prussian blue nanocube precursor; the obtained zinc iron Prussian blue nanocubes are allowed to stand for 5 days in deionized water, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0052] (2) 0.2 g of zinc iron Prussian blue nanocages were dispersed in 500 mL of deionized water to form suspension A, 0.06 g of stannous chloride was dissolved in 20 mL of 10 M concentrated hydrochloric acid to form solution B, solution B was poured into solution A under stirring, and after continuous stirring for 10 min, the solution was transferred into a 99°C oven and kept warm for 3 h. The supernatant was then discarded, and the blue precipitate was thoroughly washed and dried with deionized water and ethanol to obtain a tin-coated zinc iron Prussian blue nanocage ultra-thin hollow ridge nanocage superstructure.
[0053] (3) The obtained tin-coated zinc-iron Prussian blue nanocage ultra-thin hollow rib nanocage sample was transferred to a muffle furnace, heated to 550°C at a heating rate of 6°C / min and annealed for 1 h to obtain a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material. Its SEM image is shown in Figure 1 shown.
[0054] Example 2
[0055] A method for preparing a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material comprises the following steps:
[0056] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of a 1M potassium ferrocyanide solution; zinc chloride is dissolved in 0.5M dilute hydrochloric acid to prepare 1000 mL of a 1M zinc chloride solution; the potassium ferrocyanide solution is added to the zinc chloride solution under magnetic stirring at a speed of 130 rpm, and then stirring is continued at room temperature for 40 min to obtain a mixed suspension, which is allowed to stand for 4 h at 90° C. to obtain a yellow precipitate, which is filtered, washed, and dried at 90° C. for 8 h to obtain a zinc iron Prussian blue nanocube precursor; the obtained zinc iron Prussian blue nanocubes are allowed to stand for 4 days in deionized water, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0057] (2) 0.2 g of zinc iron Prussian blue nanocages were dispersed in 300 mL of deionized water to form suspension A, 0.14 g of stannous chloride was dissolved in 20 mL of 11 M concentrated hydrochloric acid to form solution B, solution B was poured into solution A under stirring, and after continuous stirring for 20 min, the solution was transferred into a 90°C oven and kept warm for 6 h. The supernatant was then discarded, and the blue precipitate was thoroughly washed and dried with deionized water and ethanol to obtain a tin-coated zinc iron Prussian blue nanocage ultra-thin hollow ridge nanocage superstructure.
[0058] (3) The obtained tin-coated zinc-iron Prussian blue nanocage ultra-thin hollow rib nanocage sample was transferred to a muffle furnace, heated to 420°C at a heating rate of 4°C / min and annealed for 2h to obtain a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material. The SEM image is shown in Figure 2 shown.
[0059] Example 3
[0060] A method for preparing a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material comprises the following steps:
[0061] (1) Potassium ferrocyanide was dissolved in deionized water to prepare 1000 mL of 0.1 M potassium ferrocyanide solution; zinc chloride was dissolved in 0.7 M dilute hydrochloric acid to prepare 1000 mL of 0.1 M zinc chloride solution; the potassium ferrocyanide solution was added to the zinc chloride solution under magnetic stirring at a speed of 120 rpm, and then stirred at room temperature for 30 min to obtain a mixed suspension, which was allowed to stand for 12 h at 80° C. to obtain a yellow precipitate, which was filtered, washed, and dried at 80° C. for 8 h to obtain a zinc-iron Prussian blue nanocube precursor; its SEM image is shown in FIG. Figure 3 As shown in the figure, it can be seen that it is a uniform cubic block; its XRD pattern is as follows Figure 4 As shown in the figure, the diffraction pattern proves that the prepared zinc iron Prussian blue has a strong peak and high purity. The obtained zinc iron Prussian blue nanocubes are aged in deionized water for 3 days, then fully washed with anhydrous ethanol and dried, and the obtained product is a zinc iron Prussian blue nanocage. Its SEM image is shown in Figure 5 As shown, the nanocage structure can be seen from the figure.
[0062] (2) Take 0.2g zinc iron Prussian blue nanocage and disperse it in 100mL deionized water to form suspension A, take 0.35g stannous sulfate and dissolve it in 20mL 11M concentrated hydrochloric acid to form solution B, pour solution B into A under stirring, keep it for 30 minutes, and then transfer it to an 80℃ oven for 8h. Then pour out the supernatant, wash and dry the blue precipitate with deionized water and ethanol, and obtain the ultra-thin hollow ridge nanocage superstructure of tin-coated zinc iron Prussian blue nanocage. Its SEM picture is as follows Figure 6shown.
[0063] (3) The obtained tin-coated zinc-iron Prussian blue nanocage ultra-thin hollow rib nanocage sample was transferred to a muffle furnace, heated to 350°C at a heating rate of 1°C / min and annealed for 2h to obtain a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material. Its SEM image is shown in Figure 7 As shown, its XRD Figure 8 As shown in the figure, it can be found that all diffraction peaks are consistent with the Fe4[Fe(CN)6]3 (JCPDS No.01-0239) card, and there are no other impurity peaks; the Sn element exists in an amorphous state on the surface of the zinc-iron Prussian blue nanocage. The residual Prussian blue and its analogs shown in the XRD test results provide effective physical support for the attachment of amorphous Sn elements. The product EDS diagram is shown in Fig. 9 As shown in the figure, it can be seen that the product contains zinc, iron, tin and oxygen elements, and the silicon element comes from the silicon substrate. Fig.10 As shown, its specific surface area is 520.19m 2 g -1 The average pore size is 2.37 nm, indicating that it is a porous material with a large specific surface area.
[0064] Example 4
[0065] A method for preparing a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material comprises the following steps:
[0066] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of a 0.5 M potassium ferrocyanide solution; zinc chloride is dissolved in 0.9 M dilute hydrochloric acid to prepare 1000 mL of a 0.5 M zinc chloride solution; the potassium ferrocyanide solution is added to the zinc chloride solution under magnetic stirring at a speed of 80 rpm, and then stirring is continued at room temperature for 20 min to obtain a mixed suspension, which is allowed to stand for 30 h at 60° C. to obtain a yellow precipitate, which is filtered, washed, and dried at 60° C. for 20 h to obtain a zinc iron Prussian blue nanocube precursor; the obtained zinc iron Prussian blue nanocubes are allowed to stand for 2 days in deionized water, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0067] (2) 0.2 g of zinc iron Prussian blue nanocages were dispersed in 50 mL of deionized water to form suspension A, 0.35 g of stannous chloride and 0.1 g of stannous sulfate were dissolved in 20 mL of 12 M concentrated hydrochloric acid to form solution B, and solution B was poured into solution A under stirring, and after continuous stirring for 20 min, the solution was transferred into a 70°C oven and kept warm for 12 h. The supernatant was then discarded, and the blue precipitate was thoroughly washed and dried with deionized water and ethanol to obtain a tin-coated zinc iron Prussian blue nanocage ultrathin hollow ridge nanocage superstructure.
[0068] (3) The obtained tin-coated zinc-iron Prussian blue nanocage ultra-thin hollow rib nanocage sample was transferred to a muffle furnace, heated to 300°C at a heating rate of 3°C / min and annealed for 3h to obtain a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material. The SEM image is shown in Fig.11 shown.
[0069] Example 5
[0070] A method for preparing a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material comprises the following steps:
[0071] (1) Potassium ferrocyanide is dissolved in deionized water to prepare a 1000 mL, 0.3 M potassium ferrocyanide solution; zinc chloride is dissolved in 1.2 M dilute hydrochloric acid to prepare a 1000 mL, 0.3 M zinc chloride solution; the potassium ferrocyanide solution is added to the zinc chloride solution under magnetic stirring at a speed of 50 rpm, and then stirring is continued at room temperature for 10 min to obtain a mixed suspension, which is allowed to stand for 48 h at 30° C. to obtain a yellow precipitate, which is filtered, washed, and dried at 30° C. for 24 h to obtain a zinc iron Prussian blue nanocube precursor. The obtained zinc iron Prussian blue nanocube is allowed to stand for 1 day in deionized water, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0072] (2) 0.2 g of zinc iron Prussian blue nanocages were dispersed in 10 mL of deionized water to form suspension A, 0.6 g of stannous sulfate was dissolved in 20 mL of 12.0 M concentrated hydrochloric acid to form solution B, solution B was poured into solution A under stirring, and after continuous stirring for 50 min, the solution was transferred into a 60°C oven and kept warm for 24 h. The supernatant was then discarded, and the blue precipitate was thoroughly washed and dried with deionized water and ethanol to obtain a tin-coated zinc iron Prussian blue nanocage ultrathin hollow ridge nanocage superstructure.
[0073] (3) The obtained tin-coated zinc-iron Prussian blue nanocage ultra-thin hollow rib nanocage sample was transferred to a muffle furnace, heated to 280°C at a heating rate of 2°C / min and annealed for 5h to obtain a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material. The SEM image is shown in Fig.12 shown.
[0074] Application Example 1
[0075] Application of Zn / Fe co-doped SnO2 ultrathin hollow prism nanocage superstructure composites in gas sensors
[0076] The Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material prepared in Example 3 is dispersed in anhydrous ethanol, and then evenly coated on a ceramic tube with electrodes to make a gas sensor, dried at 50°C for 2 hours, and then heat treated at 200°C for 2 hours. Then, a small nickel-chromium alloy coil is placed in the tube as a heater to provide the sensor with an operating temperature. The sensor is aged at 300°C for 48 hours, and then different volatile organic gases are tested at the operating temperature. The specific test operation steps are: use a syringe to inject a certain amount of organic vapor into the sensor test box, wait for about 2 minutes, and then introduce dry air into the test box after the sensor output response value stabilizes. The sensor output response gradually recovers, and the output response value of the sensor in dry air and with the target gas is tested and recorded using an electrochemical workstation and a computer. The sensor's sensitivity to gas response is defined as S=R a / R g (reducing gas), R a is the resistance of the sensor in dry air, R g is the resistance of the sensor in the test gas.
[0077] Performance test studies have shown that the prepared Zn / Fe co-doped SnO2 ultra-thin hollow prism nanocage superstructure composite material has a good sensitive response to common toxic and harmful organic gases in the air, such as Fig.13 As shown in the figure, it can be seen that the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material prepared by this method shows good selectivity for hydrogen sulfide compared with different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.). Therefore, it is appropriate to choose the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material as a sensitive material for H2S gas.
[0078] The above-mentioned reference embodiments provide a detailed description of a Zn / Fe co-doped SnO2 ultra-thin hollow edge nanocage superstructure composite material and its preparation method and application, which are illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material, characterized in that: The preparation method comprises the following steps: (1) preparing a zinc iron Prussian blue nanocube precursor and dispersing it in deionized water for aging to obtain a zinc iron Prussian blue nanocage; (2) dispersing zinc iron Prussian blue nanocages in deionized water to form a suspension A, dissolving stannous salt in concentrated hydrochloric acid to form a solution B, pouring the solution B into A under stirring, stirring evenly, and standing at 30-180° C. for 3-24 hours to obtain a tin-coated zinc iron Prussian blue nanocage ultra-thin hollow edge nanocage material; (3) The tin-coated zinc-iron Prussian blue nanocage ultrathin hollow rim nanocage material is annealed at 280-550°C for 1-5h to obtain a Zn / Fe co-doped SnO2 ultrathin hollow rim nanocage superstructure composite material.
2. The preparation method according to claim 1, characterized in that: In step (1), the preparation method of the zinc-iron Prussian blue nanocube precursor is: dissolving zinc salt in dilute hydrochloric acid, adding potassium ferrocyanide aqueous solution thereto, stirring until the solution becomes a yellow suspension, standing and aging at 10-95° C. for 2-36 hours, filtering, washing and drying.
3. The preparation method according to claim 2, characterized in that: The zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate and zinc nitrate; the molar ratio of potassium ferrocyanide to zinc salt is 1:
1.
4. The preparation method according to claim 2, characterized in that: The concentration of the potassium ferrocyanide aqueous solution is 0.1-2.0 mol / L; the concentration of the zinc salt in the dilute hydrochloric acid is 0.1-2.0 mol / L; and the concentration of the dilute hydrochloric acid is 0.1-1.2 mol / L.
5. The preparation method according to claim 1, characterized in that: In step (2), the stannous salt is one or both of stannous chloride and stannous sulfate.
6. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of zinc iron Prussian blue nanocage to stannous salt is 1:0.3-1.
5.
7. The preparation method according to claim 1, characterized in that: In step (2), the concentration of zinc iron Prussian blue nanocages in deionized water is 0.4-20 mg / mL.
8. The preparation method according to claim 1, characterized in that: In step (2), the concentration of stannous salt in concentrated hydrochloric acid is 3.0-15.0 mg / mL; the concentration of concentrated hydrochloric acid is 10-12 mol / L.
9. The Zn / Fe co-doped SnO2 ultra-thin hollow edge nanocage superstructure composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the Zn / Fe co-doped SnO2 ultra-thin hollow rib nanocage superstructure composite material as described in claim 9 in gas sensors.
Citation Information
Patent Citations
Hollow magnetic nano-grade composite catalytic material and preparation method thereof
CN102744067A
Preparation method of nano hollow structure prussian blue and analogues thereof
CN108133832A